The Concept Of Perennialism Education And The Flow Of Essentialism - Lovi Suciyati (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
Materialistic, atheistic and skeptical lifestyles have an impact on the emergence of hedonistic, individualistic lifestyles, therefore this problem is a challenge that requires a solution. One solution to this problem in the education sector is to instill personality or build character through a perennialist approach. The philosophy of perennialism has a concept that is at odds with materialism and mechanics. Perennialism has a concept of holistic and cyclical character development that is in accordance with the goals of education, fostering noble morals and making human beings noble. Nowadays, education faces quite serious challenges. Advances in information and communication technology are like a double-edged sword, which on the one hand brings convenience but on the other hand offers deadly poison. Challenges in the world of education are becoming increasingly difficult with the increasingly heavy onslaught of foreign culture and increasingly rapid technological advances. There are basic things that must be applied in education in Indonesia, one of which is the application of essentialism theory in education. The philosophy of essentialist education starts from truths that are considered to have been proven for centuries. In the concept of essentialism, education aims to continue cultural heritage and historical heritage through core knowledge that has been accumulated and has survived over a long period of time.